DESIGNING ACADEMIC WRITING COURSE IN RUSSIA: FOCUS ON CONTENT - Elina S. Chujkova (Obrazovanie i Nauka)
The aim of the study is to find the ways to adapt the content of Academic Writing course to Russian educational needs.Methods. The methods involve both – theoretical and empirical. Theoretical methods: the analysis of the teaching materials by English-speaking and Russianspeaking researchers in the field of EAP (English for Academic Purposes) writing, modeling, systematisation. Empirical methods: observation, interview, questioning, students’ needs analysis; longitudinal pedagogical experiment; methods of mathematical statistics.Results. Syllabus design starts with the course objectives that are quite specific with reference to writing academically in English in Russia. The author examines cultural factors that make motivation to use English for academic purposes (EAP) wane. One of them is teaching the subject which has application different from that in English-speaking countries. The author concludes that the experimental results of students’ expectations may contribute to the Academic Writing course design. They may alter both content and sequencing the material. Two main areas of academic writing application are writing for science and teaching others to write in English. The article provides a list of possible genres that vary depending on students’ professional needs.Scientific novelty. Further, developing the idea the researcher discusses three basic sources for the choice of the course material, i.e. foreign teaching EFL writing sources, printed works of Russian scholars devoted to teaching academic writing and, finally, needs analysis conducted with the Russian language students. The article provides an overview of these three sources and illustrates the main positions with the examples.Practical significance. Theoretical framework and findings may serve as a basis for organising a course of Academic Writing. For instance, a specially developed set of lectures is strongly recommended as the introduction to practice. Firstly, a lecturer obtains an opportunity to develop students’ professional motivation through the real life examples of EAP writing application in Russia. Additionally, there should be presented basic information that Russian «non-academic» students had no possibility to learn at early stages of their language education.